Simulation and optimization of a 6H-SiC metal-semiconductor-metal ultraviolet photodetector - 陈斌 杨银堂 李跃进 刘红霞 (Journal of semiconductors, 2010)
Based on thermionic emission theory,a model of a 6H-SiC metal-semiconductor-metal（MSM） ultraviolet photodetector is established with the simulation package ISE-TCAD.A device with 3μm electrode width（W） and 3μm electrode spacing（L） is simulated.The findings show that the MSM photodetector has quite a low dark current of 15 pA at 10V bias and the photocurrent is two orders of magnitude higher than the dark current.The influences of different structures on dark and illuminated current-voltage characteristics of the MSM photodetector are investigated to optimize the device parameters.Simulation results indicate that the maximum photocurrent and the highest ratio of photocurrent to dark current at 15 V bias are 5.3 nA and 327 with device parameters of W=6μm,L=3μm and W =3μm,L=6μm,respectively.